PO 18254 - Synovial giant cell tumor of the ankle - Diniz Freitas, Claudia; Araújo Pires, Eduardo; Roncatto, Carlos Eduardo; Attílio Lima Santin, Roberto (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Synovial giant cell tumor is a benign neoplasm that is rarely reported in the form of malignant metastasis. Synovial giant cell tumor most frequently occurs in the hand, hip and knee and rarely occurs in the ankle and foot. The present study describes 2 rare cases of synovial giant cell tumor located in the hindfoot (one with diffuse disease with tibiotarsal and subtalar joint involvement and the other with signs of periarticular ankle involvement) and describes the chosen treatment. Methods: Two consecutive patients were evaluated, and a brief literature review was performed. Results: Open synovectomy was performed in both cases, with complete tumor resection and satisfactory patient progression. Conclusion: Open synovectomy was found to be a good method for the treatment of these lesions because it enabled a satisfactory approach, with good visualization of the ankle compartments and underlying joints and the ability to efficiently provide marginal excision, total synovectomy and complete tumor resection for arthrotomy, without postoperative complications.